Individual Awareness of E-Wallet and Bank Staff Related Fraud in Malaysia, in the Face of Widespread Global Digitalization - Anthony Vaz; Reynold Tom Fernandez; Shaheen Mansori; Dinesh Rao (International Journal of Supply Chain Management, 2022)
The digitalised world is accelerating at a tremendous pace. Many banks and businesses today offer e-wallets as a way of paying bills. As more and more products and services are being offered online at just a click away, a major concern is the security and privacy of data that is widely being transmitted across cyberspace to support online businesses and payment activities. This is because, there are many cybercriminals who attempt to use methods to make financial gain from unsuspecting online users of apps. There is a wide array of apps available to users including the popular e-commerce applications, ride hailing apps, banking apps, travel apps, chat and social apps and many of these apps are used by cybercriminals, who plant links in such apps to trick users. The aim of this research is to gather information on the extent of e-wallet fraud and whether respondents have heard of bank staff being involved in fraud. The aim is create awareness on how the public can be more aware of the pitfalls of using e-wallet and banking online applications for day to day transactions, particularly through the use of the mobile phone to make a transaction.